First Case Report of Single Port Video-Assisted Thoracoscopic Middle Lobectomy for the Treatment of Pulmonary Aspergilloma in a Pediatric Patient - Aragón, Javier; Méndez, Itzell Pérez (European Journal of Pediatric Surgery Reports, 2013)
We present the case of an 11-year-old girl with pulmonary aspergilloma secondary to a hematologic disease successfully treated with a single port video-assisted thoracoscopic lobectomy. This surgical procedure was not previously reported. We consider this approach to be a safe and appropriate procedure for lung resection, in children or adults requiring minimal intervention and early recovery.
Keywords: single port video-assisted thoracoscopic; aspergilloma